Pengaruh Model Problem Based Learning Terhadap Hasil Belajar IPAS Materi Indonesiaku Kaya Raya Kelas 5 SD - Ningsih, Ari Kusmiati; Nasution, Nasution; Kusuma Dayu, Dian Permatasari (Jayapangus Press, 2024)
This study is motivated by the issue of low student achievement in the science subject for grade 5 students at SDN Kemiri Sidoarjo. The low achievement is influenced by instructional approaches that do not provide sufficient opportunities for students to actively engage and deeply understand the concepts. This research aims to analyze the effectiveness of the Problem Based Learning model on students' academic achievement in science for grade 5. The method used is a quasi-experimental design with a pretest-posttest control group. Data were collected through interview sheets, achievement test instruments, observations, and questionnaires. Data analysis was performed using normality tests, homogeneity tests, and t-tests to evaluate the average difference in student achievement between the experimental and control groups. The t-test results showed a t-value of 8.527, exceeding the critical value of 1.685, indicating that the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. The findings reveal that the implementation of PBL positively impacts student achievement, with significantly higher posttest scores in the experimental group compared to the control group. These results suggest that students taught using the PBL approach exhibit deeper conceptual understanding and active participation in the learning process.